USING LEAST TO MOST PROMPTING TECHNIQUES TO DECREASE NON-COMPLIANCE BEHAVIOR IN EARLY CHILDHOOD - Adelin Australiati Saragih; Ayudia Popy Sesilia (Jurnal Scientia, 2023)
This research was based on an early childhood who showed non-compliance behavior when participating in learning activities at school. The child often avoids instructions or rules given by the teacher and chooses to do activities that are different from the activities in which he is supposed to participate. The child preferred to play alone instead of doing the tasks that the teacher gives. The inconsistency of the application of regulations at school and home makes child confused and uncomfortable so this can form behavior that does not comply with the rules. This research is an experimental study using a single-subject design with reference to pre-test and post-test measurements of the interventions provided. The interventions given to child use a behavioral approach, namely by using the least to most prompting. Based on the results of the study, it was found that there were changes in behavior shown by child before and after carrying out the least to most prompting procedures. The child have begun to follow the instructions given by the teacher and follow learning activities consistently after being given interventions in the form of least to most prompting.